Bank Corporate Loan Pricing Following the Subprime Crisis - Santos, João A. C. (Review of Financial Studies, 2011)
The massive losses that banks incurred with the meltdown of the subprime mortgage market have raised concerns about their ability to continue lending to corporations. We investigate these concerns. We find that firms paid higher loan spreads during the subprime crisis. Importantly, the increase in loan spreads was higher for firms that borrowed from banks that incurred larger losses. These results hold after we control for firm-, bank-, and loan-specific factors, and account for endogeneity of bank losses. These findings, together with our evidence that borrowers took out smaller loans during the crisis when they borrowed from banks that incurred larger losses, lend support to the concerns about bank lending following their subprime losses. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.